Intra-operative phacoemulsification conversion to extracapsular cataract extraction: risk factors and visual outcome - Rathna R,; Mushawiahti Mustapha,; Amin Ahem,; Bastion MLC, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Phacoemulsification (PEA) is currently the procedure of choice for most cataract extraction. However, intra-operative complications may require the procedure to be converted to extracapsular cataract extraction (ECCE). We have evaluated the indications for conversion and visual outcomes in cases converted from phacoemulsification to ECCE. A retrospective review was performed on 33 eyes in which phacoemulsification was initiated and then converted to ECCE. The main parameters evaluated were indications for conversion and visual outcomes at 3 months. Thirty-three cases out of 1448 operations were identified from January 2013 to February 2014.The incidence of PEA converted to ECCE was 2.2%. The indications for ECCE conversion were posterior capsular rupture (PCR) in twenty-two cases, combined capsulorhexis extension with PCR in three cases, capsulorhexis extension and zonular dialysis in two cases respectively. Combined zonular dialysis with PCR, corneal toxicity, Descemet’s tear and obscured edge of capsulorhexis had one case each. Twenty-six (78%) cases had gain in vision, one (3%) case had unchanged vision and six (18%) cases had worsening of vision. The incidence of complicated phacoemulsification surgery requiring intra-operative conversion to ECCE was low in our study (2.2%). Seventy-eight percent of cases achieved final VA of 6/12 or better. Therefore, early recognition of complications and timely intra-operative conversion of PEA to ECCE may result in good visual outcome.